Flotation separation of apatite from calcite based on the surface transformation by fluorite particles. (January 2022) - Wang, Ruolin; Lu, Qianqian; Sun, Wenjuan; Lin, Shangyong; Han, Haisheng; Sun, Wei; Wei, Zhao
Highlights: Fluorite particles is an efficient depressant for calcite. Surface transformation of fluorite particles achieve the flotation separation of apatite from calcite. Calcite surface was more easily converted to fluoride than apatite surface was. The strong chemisorption of F − on mineral surface can generate a fluoride film. Abstract: The flotation separation of apatite from calcite is gordian due to the similar surface properties and calcium active sites, which make a poor selectivity in traditional fatty acid system. Pb-BHA coordination collector present great selectivity, and surface transformation by fluoride ions plays an important role in the flotation separation of salt minerals. The application of surface transformation combining with lead nitrate-benzohydroxamic acid (Pb-BHA) coordination collector can achieve the flotation separation of different calcium minerals. This study suggest that the floatability of apatite and calcite is similar without any depressants, and fluoride ions has a strong inhibiting effect on calcite but not on apatite under the Pb-BHA collector system. Zeta potential measurement determine that the surface charge of calcite obviously shift to a negative value with the adsorption of fluoride ions. X-ray photoelectron spectroscopy measurement indicates that fluoride ions is easier to adsorb on surface of calcite than that of apatite, and generate CaF2 films. Atomic force microscopy measurement illustrates the surface morphology of calcite becomes more uneven and the roughness increases obviously after the treatment of F − . Therefore, the surface transformation is meaningful to study and provides a new method for the flotation separation of calcium minerals.